The Origins and Evolution of Vertebrate Metamorphosis - Laudet, Vincent (Current biology, 2011)
Metamorphosis, classically defined as a spectacular post-embryonic transition, is well exemplified by the transformation of a tadpole into a frog. It implies the appearance of new body parts (such as the limbs), the resorption of larval features (such as the tail) and the remodelling of many organs (such as the skin or the intestine). In vertebrates, metamorphosis has been well characterized in anuran amphibians, where thyroid hormones orchestrate the intricate and seemingly contradictory changes observed at the cellular and tissue levels. Thyroid hormones control a complex hierarchical cascade of target genes via binding to specific receptors, TRα and TRβ, ligand-activated transcription factors belonging to the nuclear receptor superfamily. Metamorphosis is actually widespread in the vertebrates, though quite diverse in the way it manifests in a particular species. Furthermore, evolutionary and ecological variations of this key event, from paedomorphosis to direct development, provide an excellent illustration of how tinkering with a control pathway can lead to divergent life histories. The study of invertebrate chordates has also shed light on the origin of metamorphosis. The available data suggest that post-embryonic remodelling governed by thyroid hormones is an ancestral feature of chordates. According to this view, metamorphosis of the anurans is an extreme example of a widespread life history transition.